Application of Artificial Intelligence In Smart City - Law, Jia Wei (2021)
In the 21st century, it is not a particular case that people employ Artificial Intelligence (AI) in elements around human beings and daily social activities. Besides, studies and actual practices in foreign countries concluded that AI's implication brings a contribution to different sectors such as agricultural, governance, manufacturing, and medical field. Meanwhile, a smart city is a city concept, which is integrated with several intelligent technologies such as Big Data, sensors, and 5G connectivity. This study aims to study the effects of the implementation of AI in the smart city. The objectives of this study are to review the concepts of AI and smart city, conduct the Strength, Weakness, Opportunity, and Threat (SWOT) Analysis of deployment of AI in a smart city, and propose the future trends of AI implementation in a smart city. SWOT Analysis was conducted based on the literature review of 249 journals. The results have shown that the smart manufacturing system is the most beneficial sector from applying AI technologies. The Smart Grid (SG) and smart building systems have the most severe weaknesses due to the lack of study and AI technologies. The smart transportation system has the most opportunities to be developed and improved. Lastly, smart building and smart governance systems have the greatest potential threats to the smart city. Proposals on AI application trends in the Economic dimension are regulated Unmanned Aerial Vehicle (UAV) application, create open resources of data sources, algorithms, and sources of economic AI machines, and assist in financial analysis of the smart city. In Sociological and Political dimensions, the proposed trends are the clear definition of liability of relevant parties, lawfully-regulated-transparency of the AI models, and the cyber-attack rapid-sensing smart security system. Finally, the Technological dimension proposals are establishing individual AI databases, connections of individual AI databases with global AI databases, the combination of AI application in smart building and SG, utilization of consistent Deep Learning (DL) method in medical imaging, and implementation of fully autonomous vehicles.